The Process of Investigation and Investigation of a Notary Who Is Allegedly Committing a Criminal Act of Forgery - Soleman, Firman Satryobudi (Jurnal Konstatering, 2022)
The Indonesian state is a state based on law, therefore all aspects of the implementation and administration of the state are regulated in a system of applicable laws and regulations. In this sense, the state is implemented based on a constitution or the Constitution of the State and other legal regulations. The existence of protection for the position of a notary as an official (general) seems to be a simalakama fruit in the police investigation process in terms of criminal responsibility, the position of a notary who is full of great responsibility must be protected. On the other hand, when indications of a criminal offense have been committed by a notary, absolute law enforcement becomes a must. The obligation to maintain confidentiality is an obstacle when in this case there is an allegation of a criminal offense committed by a Notary, because it is not easy because investigators/Investigators are starting the initial stages of Investigation and Investigation related to the summons of a Notary for Examination and confiscation of minuta deed because it must be through a series of processes as stated in article 66 UUJN.Keywords: Allegedly; Forgery; Investigation.